Classification system on the selection of number of implants and superstructure design on the basis available vertical restorative space and interforaminal distance for implant supported mandibular overdenture - Akshay Bhargava; Manoti Sehgal; Sharad Gupta; Praful Mehra (The Journal of Indian Prosthodontic Society, 2016)
Purpose: The rehabilitation of the edentulous mandible is a challenge due to various limiting factors, of which the available vertical restorative space (AVRS) has been well understood in the literature. However, other anatomic variations such as arch form, arch size, and also the interforaminal distance (IFD) (due to the presence of mandibular nerve) are influential in the selection of size and position of implants, and thereby the prosthetic design. Materials and Method: In the present study, 30 edentulous patients from a group of 300 edentulous patients, representing all the three jaw relations (Class I, II, and III) were evaluated for designing a classification that could help in a comprehensive treatment plan for the edentulous mandible. Dental panoramic radiographs of each individual with a trial or final prosthesis were made. The horizontal IFD and AVRS values were calculated. Results: One-way analysis of variance followed by post-hoc test (multiple comparison) and Bonferroni method having P < 0.05 as significant value showed an overall mean of 38.9 mm for horizontal distance and 13.69 mm for the AVRS in 30 edentulous patients. Conclusion: The results showed that in the majority of cases (90%) there is insufficient space to place a bar attachment supported by five implants for mandibular overdentures. This suggests that a universal treatment plan cannot be followed due to varying anatomic factors. Hence, it becomes imperative to have a set of clinical guidelines based on the AVRS and IFD, for the selection of implant number and type of attachment. The article proposes a simple classification system based on the AVRS and IFD for establishing guidelines in the treatment planning of the edentulous mandible, to aid in selection of implant size, number, and position along with the associated prosthetic design.